The prevalence of inappropriate blood tests in pediatric patients scheduled for elective surgery in Thailand: A retrospective chart review - Naiyana Aroonpruksakul (2018)
Background: Laboratory blood tests rarely detect any abnormalities in apparently healthy patients. Moreover, unnecessary testing may not only upset pediatric patients and their parents, but may harm patients because of overtreatment of borderline or false-positive results. Objectives: To determine the prevalence and factors correlated with inappropriate preoperative testing of pediatric patients scheduled for elective surgery. Methods: We conducted a 6-month retrospective chart review of all children <15 years of age who underwent elective surgery at Siriraj Hospital in Bangkok, Thailand. Demographic and clinical data were recorded, including age, sex, physical status class according to the American Society of Anesthesiologists (ASA), underlying diseases, diagnosis, operation, service unit, and grade of surgery. The requested preoperative laboratory tests were based on the surgeon's decision. We assessed whether each test was appropriate based on the recommendations for preoperative testing from our Department of Anesthesiology. Results: We included data from 130 patients. The overall prevalence of inappropriate preoperative testing was 55%. Grade of surgery and service unit significantly affected inappropriate testing (P = 0.01 and P = 0.001 respectively). The highest prevalence of inappropriate test requests was for a complete blood count (37%), and all the risk factors, including ASA class I (P = 0.015), minor operation (P < 0.001), and nonpediatric surgery unit (P < 0.001), were significantly associated with this test. Conclusions: The prevalence of inappropriate preoperative testing was high, especially for healthy patients who underwent minor operations. Therefore, we recommend that surgical staff be educated to request laboratory tests only when indicated.